2015
DOI: 10.5194/asr-12-5-2015
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the photosynthetically active radiation under clear skies by means of a new approach

Abstract: Abstract. The k-distribution method and the correlated-k approximation of Kato et al. (1999) is a computationally efficient approach originally designed for calculations of the broadband solar radiation by dividing the solar spectrum in 32 specific spectral bands from 240 to 4606 nm. This paper describes a technique for an accurate assessment of the photosynthetically active radiation (PAR) from 400 to 700 nm at ground level, under clear-sky conditions using twelve of these spectral bands. It is validated agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…When the PAR estimates from the technique were compared against the values obtained by the detailed spectral calculations of libRadtran, Wandji Nyamsi et al [30] found no systematic bias as a function of any inputs. In addition, there was no systematic bias or trend as a function of the PAR intensity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When the PAR estimates from the technique were compared against the values obtained by the detailed spectral calculations of libRadtran, Wandji Nyamsi et al [30] found no systematic bias as a function of any inputs. In addition, there was no systematic bias or trend as a function of the PAR intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The resampling technique has been presented in Wandji Nyamsi et al [30,37] for the PAR range and UV range, respectively. The technique is a pure modelling concept with radiative transfer simulations with libRadtran.…”
Section: Description Of the Spectral Resampling And The Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations